Dividend disclosure and post-performance of REIT IPOs. Issue 2 (2nd April 2020) - Ratcliffe, Chris; Dimovski, Bill; Keneley, Monica; Salzman, Scott
ABSTRACT: When a Real Estate Investment Trust (REIT) decides to become a publicly listed entity, they are faced with a choice with regard to providing a dividend forecast in their prospectus. To date, there have been limited studies on the relationship between post-listing performance and disclosure choice. This study finds that the choice of disclosure has an important impact on REIT post-listing performance. Theoretical research argues that not all value uncertainty is resolved prior to the initial public offering (IPO) and ambiguous information quality can have long-term negative impacts on share prices. We examine the information content in the prospectuses of 114 US Equity REITs in regard to their dividend forecast between 1996 and 2017. We observe significant post-listing underperformance over the 3-, 6-, 9-and 12-month event windows for REITs that provide no dividend forecasts in their prospectus. These results suggest that the lack of distribution information has a long-term negative impact on newly listed REITs. This research has implications for both managers and investors' portfolio choices.